Potensi Asam kafeat pada Kopi sebagai Simultan Gen Peroxixme proliferator-activated receptor gamma (PPAR-γ): Studi In silico - Yohanes Bare; Maria Helvina; Agustina Elizabeth; Dewi Ratih Tirto Sari (Fakultas Pertanian, Universitas Timor, 2019)
Coffee plants are one of the cultivated plants of the Sikka Regency community. Coffee contains chemical compounds which is needed by humans. One of them is cafeic acid. Cafeic acid was recognized as having the potential as an anti-inflammatory, antioxidant, and healing type 2 diabetes mellitus (T2DM). The Peroxixme proliferator-activated receptor gamma gene (PPAR-γ) has a role in homeostasis regulation, so it can be used as hyperglycemia. But do not study on the interaction of cafeic acid as anti-diabetes molecularly. The purpose of this study was to analyze and predict the physico-chemical properties and potency of cafeic acid as anti-diabetes through the interaction of cafeic acid with PPAR- γ protein in silico. The method used consisted of downloading PPAR-γ protein through protein bank data (GDP) and cafeic acid through the PubChem database, protein preparation (PPAR-γ) and ligands (cafeic acid) with the PyRx program, protein analysis and ligand using the program using the Hex program 8.0 .0 and Discovery Studio V16.1.0.15360. The results showed that occur between cafeic acid and PPAR-γ show the role of anti-diabetes. This is evidenced by the presence of 11 amino acid residues (ASP441, LYS373, ASP396, LYS438, GLU407, PRO398, GLY399, ARG397, LEU400, GLY395, VAL403) which interacted with the chlorogenic acids and their energies of -168.5cal/mol. This function activates GLUT2 and GLUT4 as transportation routes inside and outside the cell. Caffeic acid is predicted to have potential as a natural ingredient in coffee which can be used for DMT2 therapy with genetic care (Nurtigenetics). We suggest further study is required in vivo experiment.